Rancangan Sistem Kemudi Handlebar dengan Mekanisme Rack and Pinion pada Kendaraan Disabilitas - Salim Wijaya, Michael; Subkhan, Subkhan; Sugianto, Sugianto (Jurnal Inovasi Teknologi Terapan, 2026)
Obstacles in the mobility aspect for people with disabilities can interfere with daily activities. The current era of technology has created many innovative tools and vehicles for people with disabilities, especially cars for wheelchair users. Safe and comfortable driving requires a good steering system, this can also support driving performance for people with disabilities. This research aims to support car driving performance for people with disabilities by providing new innovations in the steering system, namely the use of a portograf handlebar with a rack and pinion mechanism for movement of vehicle front wheels. The process of designing the handlebar steering system was carried in systematically using the VDI 2222 method which includes planning, conceptualizing, designing and finishing. The design results show that the portograf handlebar steering system with a rack and pinion mechanism has maximal performance based on analysis of critical components according to the needs of riders with disabilities.